Perlindungan Hukum Pencipta Lagu Daerah Makassar atas Praktik Cover Tanpa Izin - Alriyani Khusnul Hatimah; Irawati Irawati; Abdul Qahar (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2026)
ABSTRACTThe increasing use of digital platforms has intensified the practice of covering regional songs without the creator’s permission, raising concerns over copyright protection. In Makassar, unauthorized cover performances of regional songs frequently occur, often for commercial purposes, potentially infringing both moral and economic rights of the creators. This study aims to analyze the form of legal protection available to creators of Makassar regional songs and to identify factors influencing unauthorized cover practices. The research applies an empirical juridical method through statutory and sociological approaches, supported by interviews with local song creators. The results indicate that although copyright protection is regulated under Law Number 28 of 2014, its implementation remains ineffective due to weak enforcement, limited legal awareness, and the insufficient role of collective management organizations.Keywords: Legal Protection; Copyright; Regional Songs.ABSTRAKPerkembangan platform digital telah meningkatkan praktik cover lagu daerah tanpa izin pencipta sehingga menimbulkan persoalan perlindungan hak cipta. Di Kota Makassar, pembawaan ulang lagu daerah untuk kepentingan komersial kerap terjadi dan berpotensi melanggar hak moral serta hak ekonomi pencipta. Penelitian ini bertujuan untuk menganalisis bentuk perlindungan hukum terhadap pencipta lagu daerah Makassar serta mengidentifikasi faktor-faktor yang mempengaruhi terjadinya praktik cover tanpa izin. Penelitian menggunakan metode yuridis empiris dengan pendekatan perundang-undangan dan sosiologis melalui wawancara dengan pencipta lagu daerah. Hasil penelitian menunjukkan bahwa meskipun perlindungan hak cipta telah diatur dalam Undang-Undang Nomor 28 Tahun 2014, implementasinya belum efektif akibat lemahnya penegakan hukum, rendahnya kesadaran masyarakat, dan belum optimalnya peran lembaga manajemen kolektif.Kata Kunci: Perlindungan Hukum; Hak Cipta; Lagu Daerah.